Bimbingan Teknis Upaya Pengelolaan Lingkungan Pada Sekolah Dasar Untuk Mencapai Sekolah Adiwiyata - Sumarni Hamid; rasdiana zakaria (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
The Adiwiyata program is one of the Ministry of Environment's programs in order to encourage the creation of knowledge and awareness among school residents in efforts to preserve the environment. In this program it is hoped that every school member will be involved in school activities towards a healthy environment and avoid negative environmental impacts. One of the sustainable development programs in the environmental sector is environmental education which starts at the elementary, junior high, high school/vocational school levels. The aim of the Adiwiyata program is to create schools that care about the surrounding environment, which includes clean, healthy, beautiful schools and a global perspective so that school members can realize how important the environment is. Currently, elementary schools that have won Adiwiyata schools are dominated by state elementary schools. Seeing the importance of environmental education starting from the elementary school level, the adiwiyata program to create schools with an environmental perspective needs to be improved. Elementaray Telkom School Makassar is located in the Telkom Education Area along with TK Telkom, Junior high school and Senior High School. The number of students, teachers and staff growth as well as the development of educational facilities and infrastructure is quite rapid so that environmental management efforts need to be made to create clean, healthy, beautiful schools and a global-minded environment. The results of this dedication will later result in efforts to implement environmental management materials related to waste management, clean water treatment, green open space planning and biopore planning so that an environmentally sound school will be created. packaged in an interesting way will expose people who listen so that they experience an increase in knowledge.